2011
DOI: 10.1089/jop.2010.0191
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylethanolamide Effects on Intraocular Pressure After Nd:YAG Laser Iridotomy: An Experimental Clinical Study

Abstract: PEA can counteract the increase of IOP that occurs after iridotomy. It is likely that PEA controls the inflammatory process after iridotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Pescosolido et al. () administered 600 mg of microPEA (Visimast ® ) per day for 15 days. Subjects acted as their own controls, and no comment was made about possible side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pescosolido et al. () administered 600 mg of microPEA (Visimast ® ) per day for 15 days. Subjects acted as their own controls, and no comment was made about possible side effects.…”
Section: Discussionmentioning
confidence: 99%
“…One adverse event was reported and considered to be irrelevant to microPEA (Normast ® 300) exposure of 300 mg, twice a day; 26 subjects completed the study. Pescosolido et al (2011) administered 600 mg of microPEA (Visimast ® ) per day for 15 days. Subjects acted as their own controls, and no comment was made about possible side effects.…”
mentioning
confidence: 99%
“…Palmitoylethanolamide (PEA) might be a retinoprotectant, as it has cytoprotective and immune (and glia-) modulating properties and is characterized by multiple tissue-targets (mast cells, glia cells, and retina cells) [ 8 ]. PEA lowers intraocular pressure, both in normal and in high-pressure glaucoma, as well as after laser iridotomy [ 9 12 ]. In an uveitis model, PEA inhibits inflammation and protects eye tissue [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…16 Recently, a clinical study has demonstrated that PEA was effective in reducing the increased IOP after the iridotomy procedure. 17 In another clinical trial, PEA was found to significantly reduce IOP in patients diagnosed with primary open-angle glaucoma (POAG) or with ocular hypertension. 18 For the current study, the first hypothesis to be tested is that PEA may affect aqueous humor outflow.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, clinical trial studies have shown that the PEA can lower increased IOP in eyes that underwent the laser iridotomy procedure 17 and in glaucomatous eyes. 18 In the present study, we have demonstrated that administration of PEA leads to an increased aqueous humor outflow in perfused porcine anterior segments.…”
Section: Discussionmentioning
confidence: 99%